2012
DOI: 10.1007/s13181-012-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Death by Caffeine: Presumptive Malicious Poisoning of a Dog by Incorporation in Ground Meat

Abstract: Background A 4-year-old, 37 kg, male German shepherd developed hyperthermia, tachycardia, and agitation following consumption of ground meat found in the backyard of its owner. When presented to a veterinary clinic, plasma ethylene glycol (EG) testing was positive, and the dog was given ethanol and lactated Ringer's solution intravenously. Approximately 11 h postexposure the dog died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…These combined actions result in the stimulation of both the CNS and cardiac muscle, the relaxation of smooth muscle, most notably bronchial muscle, and diuresis ( 50 ). Methylxanthine poisoning cases have been reported after the ingestion of herbal supplements containing guarana ( 52 ), garden mulch made of cacao bean shells ( 53 , 54 ), caffeine tablets ( 55 , 56 ), and caffeine-containing bait ( 57 ). However, most poisoning cases occur as a result of chocolate ingestion ( 4 , 58 – 62 ).…”
Section: Methylxanthines (Caffeine Theobromine and Theophylline)mentioning
confidence: 99%
“…These combined actions result in the stimulation of both the CNS and cardiac muscle, the relaxation of smooth muscle, most notably bronchial muscle, and diuresis ( 50 ). Methylxanthine poisoning cases have been reported after the ingestion of herbal supplements containing guarana ( 52 ), garden mulch made of cacao bean shells ( 53 , 54 ), caffeine tablets ( 55 , 56 ), and caffeine-containing bait ( 57 ). However, most poisoning cases occur as a result of chocolate ingestion ( 4 , 58 – 62 ).…”
Section: Methylxanthines (Caffeine Theobromine and Theophylline)mentioning
confidence: 99%
“…Necropsies were not performed in most of the reported cases nor were caffeine levels in the blood or tissues evaluated (12,16,19,23). Two cases that received necropsies reported no gross findings, and histopathology was not done in either case (6,22). While caffeine intoxication is the most likely diagnosis, similar microscopic lesions have been attributed to seizure activity in epileptic dogs and are also seen in dogs with cardiac arrest, cranial trauma, and hypoglycemia (11,13,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of toxicosis in the medical literature have been attributed to both accidental and intentional overdose (3,4,7,14,24,25). The few case reports in dogs have been related to accidental ingestion or presumptive malicious poisoning (6,12,16,22,23). To the best of our knowledge, this is the first detailed description of the pathologic findings in canine caffeine intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…20 Ellenhorn and Barceloux 21 reported that for minor effects to be observed several mg kg −1 of compound must be ingested and serious impacts are observed above 100 mg kg −1 , with death likely above 400 mg kg −1 concentrations. Human deaths arising from metaldehyde poisoning in England and Wales have been documented by Thompson et al 22 Metaldehyde poisoning is commoner in other mammals [23][24][25][26][27] and is the second most common cause of poisoning in canines after chocolate. 28 This is thought to be due to the formulation of slug pellets which contain baits to attract molluscs; unfortunately these baits also have a tendency to attract domestic pets.…”
Section: Properties and Toxicity Of Metaldehydementioning
confidence: 99%